The Intestinal Epithelium: Central Coordinator of Mucosal Immunity. Issue 9 (September 2018) - Allaire, Joannie M.; Crowley, Shauna M.; Law, Hong T.; Chang, Sun-Young; Ko, Hyun-Jeong; Vallance, Bruce A.
Abstract : The gastrointestinal (GI) tract represents a unique challenge to the mammalian immune system. It must tolerate the presence of the luminal microbiota and thus not respond to their products, but still protect the intestinal mucosa from potentially harmful dietary antigens and invading pathogens. The intestinal epithelium, composed of a single layer of cells, is crucial for preserving gut homeostasis and acts both as a physical barrier and as a coordinating hub for immune defense and crosstalk between bacteria and immune cells. We highlight here recent findings regarding communication between microbes and intestinal epithelial cells (IECs), as well as the immune mechanisms employed by distinct IEC subsets to promote homeostasis, emphasizing the central and active role that these cells play in host enteric defense. Highlights: The intestinal epithelium is an integral component of innate immunity, defending the host by actively responding through various mechanisms that protect the mucosal barrier. IECs provide the first line of defense against noxious luminal stimuli, and professional immune cells are only activated once these defenses are overcome. The epithelium primes and signals professional immune cells to promote an effective inflammatory/immune response. The makeup of the intestinal epithelium is diverse and consists of multiple cell types (i.e., enterocytes, goblet cells, neuroendocrine cells, tuft cells, Paneth cells, and M cells), and these can develop further into specialized subsets. Through their diverse functions, these different epithelial cell types work in concert to maintain intestinal homeostasis and promote host defense.